2018
DOI: 10.3389/fmolb.2018.00083
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Intrinsically Disordered Proteins: A Problem Not Fully Appreciated

Abstract: Protein quantification is essential in a great variety of biochemical assays, yet the inherent systematic errors associated with the concentration determination of intrinsically disordered proteins (IDPs) using classical methods are hardly appreciated. Routinely used assays for protein quantification, such as the Bradford assay or ultraviolet absorbance at 280 nm, usually seriously misestimate the concentrations of IDPs due to their distinct and variable amino acid composition. Therefore, dependable method(s) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
(41 reference statements)
0
26
0
Order By: Relevance
“…It is obvious from the CD spectra and the derived α-helicity that the latter must be slightly overrated, which is most likely due to an underestimation of protein concentration. This is a general problem for IDPs due to the underrepresentation of aromatic amino acids [42]. Thus, the α-helix ratios cannot be directly compared to those derived from NMR analyses.…”
Section: Resultsmentioning
confidence: 99%
“…It is obvious from the CD spectra and the derived α-helicity that the latter must be slightly overrated, which is most likely due to an underestimation of protein concentration. This is a general problem for IDPs due to the underrepresentation of aromatic amino acids [42]. Thus, the α-helix ratios cannot be directly compared to those derived from NMR analyses.…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of XsLEA4-12, all studied proteins were able to preserve enzymatic activity upon desiccation, heat and oxidative stress in vitro , which supports the hypothesis that the high conformational changing ability correlates with protective abilities against aggregation and denaturation. It is important to highlight that since we undertook these experiments, new information on more reliable methods for IDPs quantification became available (Contreras Martos et al, 2018). As IDPs may show extreme variations in amino acid composition and physical properties, the use of more accurate quantification methods, such as ninhydrin and Qubit in combination with an absolute method, is recommended to draw more reliable conclusions about their structure.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standards for protein concentration determination are amino acid analysis and Kjeldahl analysis, but these techniques are not optimal for routine use in most labs. A recent analysis compared several different methods for determining the concentration of ordered and disordered proteins (Contreras-Martos et al, 2018). The researchers found that while the concentration of the ordered proteins using the Bradford and BCA assays were usually within 30% of the expected value, the disordered proteins show typically a >60% difference, with extreme cases having >80% difference from the expected amount.…”
Section: Idp Purificationmentioning
confidence: 99%
“…The researchers found that while the concentration of the ordered proteins using the Bradford and BCA assays were usually within 30% of the expected value, the disordered proteins show typically a >60% difference, with extreme cases having >80% difference from the expected amount. Their key result showed that the ninhydrin assay method is the best choice for determining the concentration of an IDP (Contreras-Martos et al, 2018).…”
Section: Idp Purificationmentioning
confidence: 99%